Moxibustion in patients with shoulder bursitis - Misaida Reinoso Sollet; Emilia Labrada Aguilera; Richard Garib Hernández; Eliet Cambara Pérez (Correo Científico Médico)
Introduction: Bursitis of the shoulder causes a significant limitation of movements in this joint, which implies functional disability for the patient in his daily activities.